Triacontanol Alleviated Nickel Toxicity in Maize Seedling by Controlling Its Uptake and Enhancing Antioxidant System - Abdelrazk Younis, Abeer; Ahmed Ismail, Hebatollah (Journal of Advances in Plant Biology, 2019)
Triacontanol (TRIA) role in improving growth, physiological activities and tolerance against abiotic stresses has been reported. Yet, the mechanism by which TRIA executes its effects remains elusive. This work therefore studied the possible role of TRIA exogenous application in counteracting the adverse effects of nickel (Ni) treated maize seedlings. Maize seedlings (15-day-old) were grown in washed sand irrigated with nutrient solution provided with 100 μM NiCl2. Two concentrations of TRIA (25 and 50 µM) were applied twice as a foliar spray for Ni-stressed seedlings. Shoot and root growth attributes, Ni content, and antioxidant defence systems of maize seedlings were determined. Ni treatment reduced the shoot and root length and biomass, causing necrosis of the old leaves,greater reduction was shown in the roots. The shoot and root length was negatively correlated with their Ni content, which was consistent with their content of H2O2, but not with their malondialdehyde (MDA) content. As the roots had the greatest Ni content, maximum peroxidase (PX) and glutathione reductase (GR) activity as well as the highest ascorbic acid (ASA) and reduced glutathione (GSH) content were observed in the roots. The Ni-induced deleterious effects were alleviated by foliar application of TRIA concentrations. Also, TRIA treatment minimized root Ni content, whereas it maintained the shoots unharmed by Ni. Such mitigative effects of TRIA are explained by its key role in enhancing antioxidant capacity (expressed as IC50), increased PX and ascorbate oxidase (AO) activity, GSH, and total phenolic contents.
Keywords: Triacontanol; Nickel stress; Enzymatic and non-enzymatic antioxidants; Zea mays